(untitled) - Strober, Deborah H. (Hoboken, N.J., 2007)
As he took charge of his city’s response to the 9/11 attacks, New York City's mayor Rudy Giuliani became the most admired man in America, and perhaps the world. Featuring interviews with longtime political associates, teachers, prote;ge;es, and friends, as well as his opponents, critics, and other astute political observers, Giuliani presents a living portrait of one of the most prominent and controversial politicians of our era.
Keywords: Mayors,Thị trưởng; New York,New York